2011
DOI: 10.1093/icvts/ivr027
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine in cold blood cardioplegia - a placebo-controlled study

Abstract: OBJECTIVE Adenosine as an additive in blood cardioplegia is cardioprotective in animal studies, but its clinical role in myocardial protection remains controversial. The aim of this study was to investigate whether the addition of adenosine in continuous cold blood cardioplegia would enhance myocardial protection. METHODS In a prospective double-blind study comparing adenosine 400 μmol l(-1) to placebo in continuous cold blood cardioplegia, 80 patients undergoing isolated aortic valve replacement were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
5
1
2
Order By: Relevance
“…Thus, despite demonstrating clinical benefits of adenosine to prevent cardiac ischemic injuries, due to the probability of drug-related adverse events, adenosine may not be used in patients candidate for valvular procedures, however our low study power because of small sample size and considering minimum dose of drug as a supportive, emphasizes further studies to prove or reject of our initial hypotheses. Similar to our study, Ahlsson et al in 2012 demonstrated that a combination of cold blood cardioplegia and adenosine 400 µmol/L showed no cardioprotective effects with regard to oxygen myocardial metabolism, lactate and adenine nucleotides, hemodynamic performance or postoperative enzyme release (13). No differences were found in two other large studies of pre-ischemic delivery of adenosine in either clinical performance or cardiac enzymatic release (14,15).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, despite demonstrating clinical benefits of adenosine to prevent cardiac ischemic injuries, due to the probability of drug-related adverse events, adenosine may not be used in patients candidate for valvular procedures, however our low study power because of small sample size and considering minimum dose of drug as a supportive, emphasizes further studies to prove or reject of our initial hypotheses. Similar to our study, Ahlsson et al in 2012 demonstrated that a combination of cold blood cardioplegia and adenosine 400 µmol/L showed no cardioprotective effects with regard to oxygen myocardial metabolism, lactate and adenine nucleotides, hemodynamic performance or postoperative enzyme release (13). No differences were found in two other large studies of pre-ischemic delivery of adenosine in either clinical performance or cardiac enzymatic release (14,15).…”
Section: Discussionsupporting
confidence: 90%
“…More recently, the same group showed in humans that the adenosine cardioplegia resulted in shorter times to arrest (11 vs. 44 s, P < 0.001) and lower postoperative atrial fibrillation (19 vs. 54% p = 0.01) compared with high potassium cardioplegia (20 mM) (Jakobsen et al, 2013). The discrepancy between Jacobsen's and previous adenosine cardioplegia studies (Schubert et al, 1989; Mentzer et al, 1999; Vinten-Johansen et al, 2003; Ahlsson et al, 2012) may be explained by their addition of local anesthetic (procaine) (Vinten-Johansen and Dobson, 2013). Dobson and colleagues have shown that adenosine plus a local anesthetic confers superior protection than adenosine alone (Dobson and Jones, 2004) (see Section Adenosine and Lidocaine (AL): A More Natural Way to Arrest, Protect, and Preserve the Heart).…”
Section: Five Decades Of Searching For Alternatives To Depolarizing Pmentioning
confidence: 85%
“…La miniplejia o solución de Calafiore, al carecer de otros componentes salvo sangre, potasio y magnesio, es especialmente eficaz a la vez que limita los efectos deletéreos de la hemodilución 324 Aunque se han propuesto modificaciones y aditivos a la composición de las soluciones de cardioplejia, no puede emitirse recomendación alguna ante la debilidad de la evidencia hallada, recomendándose respetar la formulación original de todas ellas; bien sean comercializadas, bien sean elaboradas en cada institución [325][326][327][328] . Si bien las soluciones de Del Nido, Custodiol, St. Thomas II o Celsior, permiten tiempos superiores al de las anteriormente citadas para la redosificación en pacientes adultos, no existe consenso sobre el protocolo de redosificación óptima, debiendo establecerse protocolos internos en cada institución basados en la literatura y respetados durante el procedimiento quirúrgico.…”
Section: Recomendación Fuerte + Nivel De Evidencia Altounclassified